PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MELALUI MODEL THINK PAIR SHARE (TPS) DI KELAS V SDN 12 PADANG BESI - Tri Mukherna, Windu; Azmi Alwi, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low narrative writing skills of fifth-grade students at SDN 12 Padang Besi. The problems were indicated by students’ difficulties in developing ideas, organizing storylines coherently, distinguishing topics and titles, and applying appropriate word choice and Indonesian spelling rules. In addition, the learning process tended to be conventional and did not actively involve students in the stages of writing. This study aimed to describe the improvement of students’ narrative writing skills through the implementation of the Think Pair Share (TPS) learning model. This research employed Classroom Action Research using qualitative and quantitative approaches and was conducted in two cycles. Cycle I consisted of two meetings and cycle II consisted of one meeting. Each cycle involved four stages: planning, implementation, observation, and reflection. The subjects of this study were a teacher and 19 fifth-grade students at SDN 12 Padang Besi. The results showed an improvement in students’ narrative writing skills. The average score increased from 72.2 in cycle I meeting 1 to 80.3 in cycle I meeting 2 and further improved to 88 in cycle II. Therefore, it can be concluded that the Think Pair Share (TPS) learning model is effective in improving the narrative writing skills of fifth-grade students at SDN 12 Padang Besi.